Between Public Health and Propaganda: Tuberculosis in Czechoslovakia in the First Decades of the Communist Regime - Rábová, Šárka Caitlín (My University, 2023)
In early postwar Czechoslovakia, medical doctors identified the fight against tuberculosis as one of their fundamental tasks, since mortality and morbidity rates from this dreaded and hardly curable disease were still high. However, the country initially struggled with a lack of special institutions and trained staff. The situation became even more complicated in 1948, when the Communist Party seized power in Czechoslovakia and transformed the organization and practice of healthcare. Focusing on the first two decades of the postwar period, this article presents the strategies used by the socialist country against tuberculosis, stressing especially the importance placed, in the development of these strategies, on having a mass impact. The most significant shifts, which concerned not only tuberculosis but healthcare in general, involved changes to the legislation. The responsibility for the health of the population was transferred to the state, which declared that it would provide free treatment and care for all citizens, regardless of their social background. During this period, the first law to prevent and control the disease was passed, and mandatory vaccination and tuberculosis treatment were introduced. As was often the case, advances in medicine were used for political propaganda, and so, in the period after 1948, tuberculosis was labelled a “capitalist disease.” This label implied that the fault for the continued presence of the disease lay at the feet of the prewar capital system. Yet as I show in the discussion below, many of these basic pillars of the fight against tuberculosis had already been established in the interwar period, and it was first and foremost the growing availability of antibiotics that helped bring this disease under control in the 1960s.
Mezi veřejným zdravím a propagandou: Tuberkulóza v Československu v prvních desetiletích komunistického režimu
Keywords: tuberculosis; vaccination; antibiotics; communist regime; Czechoslovakia; public healthcare; tuberkulóza; očkování; antibiotika; komunistický režim; Československo; veřejné zdravotnictví